Black carp TUFM collaborates with NLRX1 to inhibit MAVS-mediated antiviral signaling pathway. (September 2021) - Cao, Yingyi; Chen, Zhaoyuan; Huang, Jiayi; Wu, Hui; Zou, Jun; Feng, Hao
Abstract: TUFM is a mitochondrial protein and serves as a regulator of antiviral signaling; nevertheless, the character of TUFM in teleosts remains unidentified. In this study, TUFM homologue of black carp ( Mylopharyngodon piceus ) has been characterized and its role in innate immunity has been explored. Black carp TUFM (bcTUFM) comprises 447 amino acids and shows the high similarity to human TUFM. bcTUFM was about 50 kDa in the Western blot assay and was determined as a cytosolic protein by immunofluorescent microscopy. Knockdown of bcTUFM by shRNA enhanced the antiviral ability of the host cells. The induction fold of interferon promoter transcription in the cells co-expressing bcTUFM and bcMAVS was much lower than that of the cells expressing bcMAVS alone. Our previous study has identified that bcNLRX1 interacted with bcMAVS and functioned as an inhibitor of bcMAVS. The interaction between bcTUFM and bcNLRX1, but not bcTUFM and bcMAVS, was detected through co-immunoprecipitation. The subsequent reporter assay and plaque assay demonstrated that the inhibition of bcMAVS-mediated interferon production and antiviral activity by bcNLRX1 was enhanced by co-expressed bcTUFM. Thus, our data suggests that bcTUFM cooperates with bcNLRX1 to inhibit bcMAVS-mediated antiviral signaling during host antiviral innate immune response against SVCV. Highlights: bcTUFM associates with bcNLRX1 but not bcMAVS. bcTUFM synergizes with bcNLRX1 to inhibit bcMAVS-mediated IFN production. bcTUFM cooperates with bcNLRX1 to inhibit bcMAVS-mediated the antiviral activity against SVCV.